EDITORIAL COMMENT: Police for the Community - Suprihanto, Eko; Winarno, Hady; Suhendarwan, Bhakti; Setyawan, Nugroho Ari; Syahrial, Taufiq; Farid, Muhammad Imam; Muchtar, Jarot (Indonesian National Police Academy, 2025)
This editorial comment is the introduction for this collection with the title “Police for the Community”. The police are for the community. The various practices on how the police deliver services to communities were presented in the articles. Community policing and problem-oriented policing are the terms that are closely associated with “the police for the community”. The editors discuss the concept of community policing and problem-oriented policing. Afterwards, a brief explanation of the articles is given. There are several potential lessons to be learned from this collection for the future development of the police academy, ensuring that the police serve the community effectively.